2008
DOI: 10.21608/jhiph.2008.20911
|View full text |Cite
|
Sign up to set email alerts
|

Trends and Determinants among Cardiac Disabled Workers in Alexandria

Abstract: Background: The present study was designed to investigate the trend and determinant factors among cardiac disabled workers presented in the years 2003-2005 at Health Insurance Committee for disability rating in Alexandria and to compare the currently used system with others. Methods: A retrospective study was conducted to review complete records for those below the age 65 years. The available data were coded to include age, gender, job title, disabling symptoms, presence or absence of abnormal findings in rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
1
0
0
Order By: Relevance
“…In relation to patient's residence, the results of the present study agree with study by Fahmy et al 19 who reported that in Egypt, heart failure is more common in rural than urban regions because rural regions deprived from medical education about risk factors, signs and symptoms of disease and ways of management.…”
Section: Discussionsupporting
confidence: 91%
“…In relation to patient's residence, the results of the present study agree with study by Fahmy et al 19 who reported that in Egypt, heart failure is more common in rural than urban regions because rural regions deprived from medical education about risk factors, signs and symptoms of disease and ways of management.…”
Section: Discussionsupporting
confidence: 91%